Investigation of the structural properties of porous material according to the sorption isotherms and drainage curves - Holubets, T. (Publishing House of Lviv Polytechnic National University, 2016)
In this paper in the compliance with the method of the local averaging, the basic relations of surface physics and thermodynamics for the description of diffusion process of the liquid and gas phases in the inhomogeneous porous media have been considered. In line with the drainage and sorption properties of the liquid in the porous skeleton, the normalized function of distribution of the pore size for the effective radius has been defined. The relations for the determination of the intrinsic and relative permeability of phases in the solid skeleton have been proposed. The dependence of the intrinsic permeability on the structural properties of porous material has been analyzed. A simple condition of the equilibrium of phases in the porous skeleton with surrounding medium has been obtained. У данiй статтi, вiдповiдно до методу локального просторового усереднення, розглянуто основнi спiввiдношення фiзики поверхнi i термодинамiки для опису процесiв дифузiї рiдкої або газової фаз в неоднорiдному пористому середовищi. Згiдно з дренажними або сорбцiйними властивостями рiдини у пористому скелетi означено нормовану функцiю розподiлу розмiру пор за ефективним радiуском. Запропоновано спiввiдношення для визначення абсолютної i вiдносної проникностi фаз у твердому скелетi. Проаналiзовано залежнiсть абсолютної проникностi вiд структурних властивостей пористого матерiалу. Отримано просту умову рiвноваги фаз у пористому скелетi з оточуючим середовищем.
Дослiдження структурних властивостей пористого матерiалу згiдно з iзотермами сорбцiї або дренажних кривих
Keywords: porous materials; adsorption; capillary phenomena; diffusion of gas and liquid; пористi матерiали; адсорбцiя; капiлярнi явища; дифузiя газу i рiдини